Traumatic abdominal wall hernia and bowel perforation leading to shock: a case report - Ali, Nasir; Rayoo, Shavi; Kaleem, Aina; Singh, Tanisha; Hussain, Zahur (International Surgery Journal, 2024)
Traumatic abdominal wall hernia (TAWH) is a rare clinical entity resulting from blunt force trauma that disrupts the abdominal wall muscles and fascia, leading to the protrusion of intra-abdominal contents without skin penetration. It accounts for approximately 0.07% of all abdominal trauma cases and often presents diagnostic challenges due to its rarity and association with other injuries. We present a case of a 66-year-old male who presented with a TAWH and small bowel perforation after being struck by a bull. He exhibited hemodynamic instability and abdominal tenderness. Imaging revealed a strangulated hernia. Surgical exploration found a 5 cm abdominal wall defect with herniated, gangrenous small bowel, with jejunal perforation. The affected bowel segment was resected, and the abdominal wall was repaired. The patient stabilized postoperatively and was discharged on day 14. TAWH requires a high index of suspicion for diagnosis, especially in the presence of blunt abdominal trauma. Immediate surgical intervention is often necessary to prevent complications such as bowel strangulation and peritonitis. This case underscores the importance of early recognition and timely surgical management to improve outcomes in patients with TAWH complicated by bowel perforation. Early diagnosis and prompt surgical intervention are crucial in managing TAWH, particularly when accompanied by bowel perforation. This case highlights the need for vigilance and rapid response in emergency settings to mitigate the significant morbidity and potential mortality associated with this rare condition.